Molecular subtype shift in breast cancer upon trastuzumab treatment: a case report - Āboliņš, Arnis; Vanags, Andrejs; Trofimovičs, Genadijs; Miklaševičs, Edvīns; Gardovskis, Jānis; Štrumfa, Ilze (Polish Journal of Pathology, 2011)
Breast cancer is the most common cancer in women. The mortality remains significant despite advanced treatment possibilities. The management of breast cancer is guided by immunohistochemical data that are summarized into molecular subtypes, namely, luminal A, luminal B, HER2 positive and triple negative. HER2 positive and triple negative subtypes of breast cancer are considered to be biologically distinct. We present a case of clinically aggressive breast cancer in a 58-year-old female. Along the course of the disease, the molecular type switched from HER2 positive to triple negative. The patient deteriorated despite combined therapy. We recommend making a possible change of the molecular subtype and employing repeated immunohistochemical investigation in case of relapse.